Potensi Pasang Surut Lahan Rawa untuk Pengembangan Irigasi di Kabupaten Merauke Menggunakan Pemodelan Hidrodinamika 1D2D - Yudi Lasmana; Parlinggoman Simanungkalit; Muhammad Gifariyono; Ganggaya Sotyadarpita; L. Budi Triadi (JURNAL TEKNIK HIDRAULIK, 2018)
Development of agriculture in lowland areas in Merauke Regency of Papua Province has been undertaken by both the Government and the community. However, the existing condition shows during the dry season the rice fields are drought so that it can only be one time a year. This is because the water needed to irrigate the land relies on water from the tides while the highest water when the tide has not been able to enter the land. Merauke District has three major rivers, namely Bian River, Kumbe River and Maro River, the three rivers are the source of water that can be the potential to overcome this problem. Therefore, a study was conducted to determine the potential of ups and downs of the River BIKUMA as input in the development of lowland irrigation in Merauke Regency. This study is supported by hydrometry and hydraulic surveys conducted during the dry season during spring tide and neap tide simultaneously for all three rivers. The survey included measuring river geometry activities with a range of 5 Km, river hydrometry measurements (observation of water fluctuations with proportional distances for model calibration and upstream river velocity for discharge). Limitations of river upstream measurements are limited by the distance of the Bian River 125 Km, the River Kumbe along the 171 km, and the Maro River along 66 km. Then performed a 1D2D hydrodynamic mathematical modeling that describes the movement of water from upstream to downstream. From the results of modeling is known that the water entering from the sea to the Bikuma River is greater than the water out to sea. The potential for tides is 1.7 M m3. Furthermore, the simulation of Sobek 1D2D obtained the extent of natural condition, the area that can be inundated is 123.609 ha. Utilization of tidal potential can be channeled to the development of lowland irrigation in Merauke. Upper tidal energy in the upstream can be directed to the development zone location through an integrated lowland irrigation water management system so that water utilization can be optimal.